Revealing the Concept of Mother Earth in the Qur'an: A Thematic Tafsir Study and Its Theological and Practical Implications - Tita Yuliawati; Muhammad Alif Fathullah Azhar; Ilzam Hubby Dzikrillah Alfani; Mukhsin, Mukhsin; Asya Dwina Luthfia (STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
The global environmental crisis has heightened attention to the concept of Mother Earth across various disciplines, including religious studies. This study aims to analyze the interpretation of Qur'anic verses regarding the relationship between humans and nature and to explore how these interpretations can be articulated within the framework of the Mother Earth concept. The method used is a literature review with content analysis of classical (Ath-Thabari) and contemporary (Al-Munir) interpretations of key verses, namely Q.S. Hud [11]: 61, Q.S. Al-A’raf [7]: 57-58, and Q.S. Ar-Rum [30]: 41. The findings reveal that while the term Mother Earth is not explicitly mentioned in the Qur'an, Islamic teachings present a comprehensive perspective on the human-nature relationship that resonates with the essence of this concept. The analyzed verses indicate humans' position as stewards and caretakers of the earth, the reciprocal relationship between humans and nature, and nature as a sign of God's power. This study concludes that the concept of Mother Earth aligns with the Qur'anic principles of environmental preservation and can serve as a practical foundation for equitable and wise environmental management and conservation efforts. The novelty of this research lies in integrating the concept of Mother Earth with Qur'anic interpretations, offering a new perspective on understanding the human-nature relationship within the context of Islam.